Fear of predators alters herbivore regulation of soil microbial community function - Wei Tian; Dror Hawlena; Jordi F. Pagès; Zhiwei Zhong; Deli Wang (Ecology and Evolution)
Abstract Fear of predation can affect important ecosystem processes by altering the prey traits expression that, in turn, regulates the quantity and quality of nutritional inputs to soil. Here, we aimed to assist in bridging a knowledge gap in this cascading chain of events by exploring how risk of spider predation may affect grasshopper prey performances, and the activity of various microbial extracellular enzymes in the soil. Using a mesocosms field‐experiment, we found that grasshoppers threatened by spider predation ate less, grew slower, and had a higher body carbon to nitrogen ratio. Herbivory increased activity of all microbial extracellular enzymes examined, likely due to higher availability of root exudates. Predation risk had no effect on C‐acquiring enzymes but decreased activity of P‐acquiring enzymes. We found contrasting results regarding the effect of predation on the activity of N‐acetyl‐glucosaminidase and leucine arylamidase N‐acquiring enzymes, suggesting that predation risk may alter the composition of N‐inputs to soil. Our work highlighted the importance of soil microbial enzymatic activity as a way to predict how changes in the aboveground food‐web dynamics may alter key ecosystem processes like nutritional‐cycling.